Determinants and Impact of Child Marriage on the Bride in Indonesia - Nunik Puspitasari (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study aims to analyze variables thought to be determinants and effects of child marriage on the bride.The design of this study was a case-control study. The number of samples was 116 brides consisting of 58brides married at age <18 years old as a case group and 58 brides who got married at age> 18 years old as acontrol group. There were 23 variables thought to be determinants and nine variables suspected as the impactof child marriage. The variables that were significantly associated with child marriage were 1) the ethnicof the bride, 2) father’s education, 3) mother’s education, 4) the occupational of the bride, 5) education ofthe bride and 6) the purpose of marriage was to lived happily (psychological). While the variables that weresignificantly affected the child marriage were: 1) the bride’s education and 2) the purpose of marriage wasto lived happily (psychological). Variables that significantly to the impact of child marriage were women’sindependence or women’s autonomy. The determinants of child marriage were the bride’s education, andthe purpose of marriage was to lived happily (psychological). The impact of child marriage was women’sautonomy.